2010
DOI: 10.1111/j.1365-2605.2009.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of PMCA4 in bovine sperm membrane fractions

Abstract: The plasma membrane Ca(2+) -ATPase (PMCA) is the main restorer of Ca(2+) balance in sperm. Particularly, PMCA isoform 4 has an essential function in sperm fertility by its participation in gaining sperm hypermotility. PMCA activity is influenced by its lipid environment. Sperm membranes exhibit lipid raft microdomains or detergent-resistant membrane domains, enriched in sphingolipids and cholesterol, forming functional specialized areas. Lipid and protein composition of lipid rafts alters during the capacitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…It has also been shown in mice that PMCA4 is the major isoform in testis (90%) and is located in the principal piece of sperm tail (7). In bovine sperm we could show that PMCA4 localizes to the mid piece of caput and cauda sperm (42). Using in situ hybridization and immunohistochemistry to study the gene expression and distribution of PMCA4 protein in bovine germ cell stages, we found clear evidence that PMCA4 mRNA expression is restricted to spermatogonia and early primary spermatocytes.…”
Section: Consequences Of Differential Pmca4 Splice Variant Localizatimentioning
confidence: 51%
“…It has also been shown in mice that PMCA4 is the major isoform in testis (90%) and is located in the principal piece of sperm tail (7). In bovine sperm we could show that PMCA4 localizes to the mid piece of caput and cauda sperm (42). Using in situ hybridization and immunohistochemistry to study the gene expression and distribution of PMCA4 protein in bovine germ cell stages, we found clear evidence that PMCA4 mRNA expression is restricted to spermatogonia and early primary spermatocytes.…”
Section: Consequences Of Differential Pmca4 Splice Variant Localizatimentioning
confidence: 51%
“…Cholesterol inclusion works to increase the thickness and order of plasma membranes [51] and it has been suggested that some membrane domains are formed only in the presence of certain concentrations of cholesterol [52]. Lipid rafts are enriched in cholesterol, sphingomyelin, lipids with saturated long chain acyl chains, [1] and in sperm, the plasma membrane which lays over the acrosome displays rafts enriched in gangliosides and cholesterol [53, 54]. Cholesterol content of membranes both above and below native membrane content (16 moL% of total lipids) decreases Na + K + -ATPase activity in PC liposomes using pig kidney ATPase [47].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts contain lipids, glycosylphosphatidylinositol- (GPI-) anchored proteins and various signal transduction proteins [1, 2] that engage the microdomain in cell signaling and cell adhesion events [3]. Capacitation is a process whereby spermatozoa gain the ability to fertilize through a series of membrane changes including a reorganization of membrane lipids and proteins [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The homogenate was centrifuged for 10 min at 14,000 × g at 4°C, and the supernatant subjected to ultracentrifugation at 100,000 × g for 60 min at 4°C to yield microsomes. The pellet was re-suspended for 15 min at 4°C in 100 μl of homogenization buffer containing 1.5% n-octyl-β-d-glucopyranoside as described (Post et al, 2010), and protein concentration was determined using the BCA kit mentioned above. Ca 2+ -ATPase activity was determined as described (Kosk-Kosicka, 1999) for the enzymatic hydrolysis rate of ATP via quantitation of the resulting inorganic phosphate (P i ), as a function of time.…”
Section: Methodsmentioning
confidence: 99%